Isolation and Identification of Saprolegnia Parasitica and Other Fungi from Farms Fishes in the Province of Wasit / Iraq - Isa S Touhali (Journal of Global Pharma Technology, 2018)
Background: Fungal infections are one of the main factors responsible for mortality and economic losses among the ornamental and food fish farming industries. The most commonly identified fungal pathogens of fish are water molds of Saprolegnia genus. Objective: The goal of this study was to determine the presence of Saprolegnia species in the fish farm by utilizing traditional and molecular strategies and contribute to the knowledge of fungal biodiversity in the province of Wasit. Methods: This study included a total of one hundred samples were collected during the six months from September -2016 to February -2017 from fish culture ponds. in the province of Wasit , Iraq. After isolation of fungi by culturing and examination under microscopic by used special stains was showed 42 (42%) samples were positive for fungal growth. Out of 42 fungal growths; 13 (31%) isolates were identified as Saprolegnia species were identified in this study. Also other fungi were isolated; 11(26.2%) isolates were identified as Aspergillus sp.; 8 (19%) isolates were identified as Penicillium sp.; 6 (14.3%) isolates were identified as Alternaria sp.; 4 (9.5%) isolates were identified as Fusarium sp. and used specific primers sequences (ITS1 and ITS4) to detection Internal transcribed spacer (ITS) gene of Saprolegnia parasitica were used in conventional PCR. The results of the PCR amplification of (ITS) gene showed that, 8 samples out 13 samples Saprolegnia species were positive to Saprolegnia parasitica with a PCR product size of approximated 750 bp, while 5 samples out 13 samples Saprolegnia species showed negative results for the presence of this gene as indicated by the absence of the PCR products in their relevant lanes. In conclusion, the cultured fishes frequently suffer from fungal disease, especially during the months from early December to late February when water temperature falls below 10°C and several species of Saprolegnia cause several damages in fishes and economic losses for the aquaculture industry. However, with early diagnosis by culturing and molecular technique and appropriate management, has a good prognosis.Keywords: Saprolegnia species, Saprolegnia parasitica, fish culture ponds, Internal transcribed spacer (ITS) gene.